Green synthesis and application of GO nanoparticles to augment growth parameters and yield in mungbean (Vigna radiata L.) - Mirza, Faisal Shafiq; Aftab, Zill-e-Huma; Ali, Muhammad Danish; Aftab, Arusa; Anjum, Tehmina; Rafiq, Hamza; Li, Guihua (Frontiers in Plant Science, 2022)
Plant growth promotion has long been a challenge for growers all over the world. In this work, we devised a green nanomaterial-assisted approach to boost plant growth. It has been reported that carbon nanomaterials are toxic to plants because they can inhibit the uptake of nutrients if employed in higher concentrations, however this study shows that graphene oxide (GO) can be used as a regulator tool to improve plant growth and stability. Graphene oxide in different concentrations was added to the soil of mungbean. It is proved that when a suitable amount of graphene oxide was applied, it had a good influence on plant growth by enhancing the length of roots and shoots, number of leaves, number of root nodules per plant, number of pods, and seeds per pod. We presume that the use of bio-fabricated graphene oxide as a strategy would make it possible to boost both plant growth and the significant increase in the number of seeds produced by each plant.